State of the knowledge of the flooded savanna ecosystems of Orinoquia Colombiana (Orinoquia, 2015)
Flooded savannas are 12.5% of the Orinoco basin, a strategic ecosystem of great economical, biological, and ecologic importance. The aim of our study was to update and inform the reader on the state of knowledge of the ecosystems associated to flooded savannas of the Colombian Orinoquia. We worked on the following theme categories: ecosystem studies, flora and fauna, sustainable conservation and use, planning and management tools, and environmental education. We analyzed information according to publication type: scientific paper, book, book chapter, technical report, theses, and summaries. We included a total of 159 publications. 53% of the literature has been officially published, while the remaining 47% is still unpublished. The largest amount of publications corresponds to ecological studies, and flora and fauna (68%). In general, we consider that better structured studies are lacking, ones that include savanna ecosystems, and their associated vegetation, since most of the studies have centered on riparian forests. The decades of 1990-2000 and 2000-2010 harvested the largest amounts of literature. We confirmed our previous hypothesis about the lack of information on flooded savanna ecosystems. Some taxonomic groups have been more thoroughly studied than others. Seasonality is a determinant factor on the hydrologic dynamic of these savannas. Thus, we consider imperative to start working on hydrologic regulation services, and their importance on the dynamic and ecological processes. It is indispensable to further improve the knowledge, use and conservation of the flooded savannas of the Colombian Orinoquia, because this ecosystem is strategic for the hydrologic dynamic of the third most important river system in the World: the Orinoco basin.Key Words: ecosystems; flora; fauna; Orinoco; hydrologic dynamic.
Keywords: ecosystems; flora; fauna; Orinoco; hydrologic dynamic.